Analisis Model Pengelolaan Dana Zakat di Indonesia (Kajian Kualitatif Eksistensi Badan Amil Zakat dan Lembaga Amil Zakat) - Khasanah, Umrotul (ULUL ALBAB Jurnal Studi Islam, 2005)
Theoretically, poverty is a phenomenon brought about by practices of economic policy that deviates the principle of equilibrium. Islam regards the economic discipline (the use of productive resources by taking into accounts of cost efficiency and most advantages of social utilily) as part of equilibrium in social responsibility. Economic function as part of social responsibility is urgently demanded by Islam in order to achieve a harmonious equilibrium in the relationship between the haves and the haves- not. In Islam, many social responsibility mechanisms can be performed among others through zakah, infak, sedekah, wakaf, jizyah, kharaj, rikaz, ghanimah, and so forth. This thesis pays attention to the problems of zakah fund management. In this research, it was found that there are four kinds of zakah fund raisers, namely the bureaucratic model, the business model, the non-government organization model (NGO/ormas) dan the traditional model zakah fund raising agents or institutions.